Decreased baroreflex sensitivity is linked to sympathovagal imbalance, body fat mass and altered cardiometabolic profile in pre-obesity and obesity - Indumathy, Jagadeeswaran; Pal, Gopal Krushna; Pal, Pravati; Ananthanarayanan, Palakkad Hariharan; Parija, Subash Chandra; Balachander, Jayaraman; Dutta, Tarun Kumar (Metabolism, clinical and experimental, 2015)
Though decreased baroreflex sensitivity (BRS), the predictor of cardiac morbidities and mortality has been reported in obesity, the mechanisms and metabolic biomarkers influencing BRS have not been studied. We aimed to assess the difference in cardiovascular (CV) risk profile in pre-obesity and obesity, and the contribution of body composition and cardiometabolic factors to CV risks in these two conditions. Obesity indices, body composition, blood pressure variability and autonomic function test parameters were recorded in 223 subjects divided into controls (n=72), pre-obese (n=77) and obese (n=74) groups. Insulin resistance (HOMA-IR), atherogenic index (AI), leptin, adiponectin, inflammatory and oxidative stress parameters were measured. Association and independent contribution of altered cardiometabolic parameters with BRS were performed by Pearson’s correlation and multiple regression analysis, respectively. BRS was significantly decreased in pre-obese and obese group compared to controls. Sympathovagal imbalance (SVI) in the form of increased sympathetic and decreased parasympathetic cardiac drives was observed in pre-obesity and obesity. There was significant difference in general markers of obesity (body mass index, and waist-to-hip ratio), between pre-obese and obese group, however no such difference was observed in body composition and cardiometabolic parameters between the two groups. AI, high sensitive C-reactive protein (hs-CRP) and ratio of basal metabolism to body fat (BM/BF) in pre-obese group, and AI, HOMA-IR, leptin, adiponectin, ratio of basal metabolism to body weight (BM/BW), BM/BF, inflammatory and oxidative stress markers in obese group had independent contribution to BRS. Among these metabolic biomarkers, BRS had maximum association with leptin (β=0.532, p=0.000) in the obese group and hs-CRP (β=0.445, p=0.022) in the pre-obese group. The present study demonstrates decreased BRS, an important marker of increased CV risk in pre-obesity and obesity. The intensity of cardiometabolic derangements and CV risk was comparable between pre-obese and obese subjects. BM/BF ratio appears to be a better marker of metabolic activity in pre-obesity and obesity. SVI and increased basal metabolism appear to be the physiological link between metabolic derangements and CV risks in both pre-obesity and obesity.